A structural analysis of destination brand equity in mountainous tourism destination in northern India. (October 2019) - Kaushal, Vikrant; Sharma, Suman; Reddy, G Mahender
The present study attempts to develop a destination brand equity model for mountainous tourism destination based in a north Indian state of Uttarakhand. Brand equity research in leisure studies has been gaining increased scholarly attention, yet similar researches in Indian context are almost non-existent. This contemporary brand assessment area of enquiry has been considered in the present research by exploiting six dimensions structure including destination brand awareness, destination image, social self-image, perceived quality, perceived value and destination loyalty. Findings in particular stress on the relevance of three vital antecedents, namely, destination image, perceived value and social self-image in improving tourist loyalty. It is suggested that price benefit trade-off is duly considered for improving tourist loyalty, and the hilly attractions exhibit potential to augment tourists' self and social images. If exploited appositely, destination image, social self-image and perceived value may engender a stronger loyalty bond between visitors and destination. With the aid of structure equation modelling, pertinent relationships rooted in the brand equity theory have been tested and few newer linkages have been uncovered and validated. The paper concludes with vital implications, limitations and scope of future research.